Pertanggungjawaban Notaris Terhadap Akta Yang Tidak Dibacakan - Muhammad Alfatah; Anne Gunawati; Wira Pranciska (Jurnal Nuansa Kenotariatan, 2017)
One of the obligations of a Notary is to read the deed before the audience that must be done by a Notary (Article 16 paragraph (1) letter m Laws Notary Department). The method used in this studys a normative juridical approach supported in an empirical juridical. The data used is secondary data consisting of primary legal materials, secondary legal materials, tertiary legal materials. For data analysis performed with qualitative juridical analysis method. The author can conclude that: due to the deed not read by a Notary can be subject to responsibility, namely civil responsibility. This is the deed has decreased in quality, the position of the deed is lower in strength as a means of proof, the previous one is complete and perfect is the beginning of proof, the proof power cannot prove anything